Incidence of Galactorrhea in Young Women Using Depot-Medroxyprogesterone Acetate - Hatim A. Omar; Rana M. Zakharia; Shibani Kanungo; Marlene Huff; Kimberly McClanahan (The Scientific World Journal)
Galactorrhea is rarely mentioned as a possible side effect of the use of Depot-Medroxyprogesterone Acetate (DMPA). Over the last few years, we have noticed an increased number of patients complaining of galactorrhea. A review of clinical data showed that between 1999 and 2005, 360 adolescents in our clinic used DMPA for at least 6 months. After medical follow-up, 13 (3.6%) of these patients were found to have developed galactorrhea. The mean age of the patients was 19.4 years with a range from 13—24. Prolactin levels in these patients were normal, and in all subjects, the galactorrhea resolved spontaneously within the next year in both patients who continued use and those who discontinued use of DMPA. It appears that galactorrhea is a benign side effect and as previous reports have suggested, it did not seem to be related to changes in Prolactin levels in our patients. It is thought that this is a progesterone-mediated effect. We believe that reassurance and education of patients is sufficient and there is no evidence of need for further intervention. Since the sample size is small in this study, additional research is recommended as to validate the presence of progesterone-mediated effects secondary to the use of DMPA.